The Concept of Time in the Works of Modernists - Khachibabyan, Mane (Տիգրան Մեծ)
Time is an important matter of study in science, religion, philosophy, art and literature. The is-sues that interest scholars and theorists are reflected in the art and literature as well, since those are the embodiments of society, its mind, life and issues. Historical traditions, economic, social and political features have huge impact on the perceptions of concepts and theories. This article aims to identify the relationship between the concept of time and art/literature. Through analysis of the works of modernist artists and authors the article will showcase the representations of the concept of time in the works of Charles Baudelaire, Salvador Dali, Walter Benjamin and Henri Bergson.
Keywords: Philosophy